Decrease in serum interleukin-21 levels is associated with disease activity improvement in patients with recent-onset rheumatoid arthritis - Sglunda, Ondřej; Mann, Heřman; Hulejová, Hana; Pecha, O; Pleštilová, Lenka; Růžičková, Olga; Fojtíková, M; Šléglová, Olga; Forejtová, Šárka; Pavelka, Karel; Vencovský, Jiří; Šenolt, Ladislav (Physiological research, 2014)
Interleukin-21 (IL-21) plays an important role in the pathogenesis of rheumatoid arthritis (RA). The aim of our study was to assess serum levels of IL-21 in patients with recent-onset RA in relation to disease activity and response to treatment. We analyzed serum levels of IL-21 in 51 RA patients, both before and 12 weeks after the initiation of treatment and in 36 healthy individuals. Disease activity was assessed at baseline and at weeks 12 and 24 using the Disease Activity Score for 28 joints, serum levels of C-reactive protein, and the total swollen joint count. We found that IL-21 levels were not increased in patients with recent-onset RA compared with healthy controls, but they had significantly decreased from baseline to week 12 during treatment. Baseline levels of IL-21 significantly correlated with measures of disease activity (p<0.02 for all). Although IL-21 levels did not predict achievement of remission, decrease in IL-21 levels correlated with improvement in disease activity after 12 weeks (p<0.02) and also after 24 weeks (p<0.04) of treatment. Our data suggest that circulating IL-21 levels may serve as a biomarker of disease activity and better outcome in early phase of RA.
Keywords: antirevmatika; mladý dospělý; dospělí; revmatoidní artritida; Antirheumatic Agents; Humans; interleukiny; Adult; Interleukins; lidé středního věku; Joints; Female; klouby; Middle Aged; Aged; Biomarkers; výsledek terapie; Treatment Outcome; Male; senioři; ženské pohlaví; Arthritis, Rheumatoid; Young Adult; biologické markery; lidé; mužské pohlaví